The EFFECT OF QUALITY OF WORK LIFE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN PT. TASPEN (PERSERO) BANDUNG BRANCH - Yuliati Indah, Dewi; Damayanti, Zelina (Journal of Business and Management Inaba, 2022)
The phenomenon that occurs in employees of PT. Taspen Main Branch Office Bandung is decreasing employee performance, so it does not reach its work target. The research aims to identify and analyze, 1). quality of work life 2.) job satisfaction 3) employee performance, 4) the magnitude of the influence of quality of work life and job satisfaction on employee performance either simultaneously or partially. , the population in this study were 49 employees, and the sample was saturated. Data collection techniques used are observation, interviews and questionnaires. The data analysis methods used are validity and reliability tests, multiple linear regression analysis, multiple correlation analysis, and the coefficient of determination. Based on the results of the analysis, simultaneously the effect of quality of work life and job satisfaction on performance is positive and significant. While the results of the partial analysis, the job satisfaction variable has the most dominant influence value compared to the quality of work life variable.